Evaluation of a Pet-Assisted Living Intervention for Improving Functional Status in Assisted Living Residents With Mild to Moderate Cognitive Impairment: A Pilot Study. (May 2015) - Friedmann, Erika; Galik, Elizabeth; Thomas, Sue A.; Hall, P. Sue; Chung, Seon Yoon; McCune, Sandra
Background: In older adults with cognitive impairment (CI), decreased functional status and increased behavioral symptoms require relocation from assisted living (AL) to nursing homes. Studies support positive effects of pets on health/function. Purpose: Evaluate the effectiveness of the Pet AL (PAL) intervention to support physical, behavioral, and emotional function in AL residents with CI. Methods: Cognitively impaired AL residents randomized to 60-90 minute sessions [PAL (n = 22) or reminiscing (n = 18)] twice/week for 12 weeks. PAL interventionist encourages residents to perform skills with the visiting dog; reminiscing interventionist encourages residents to reminisce. Monthly assessment of physical (energy expenditure, activities of daily living), emotional (depression, apathy), and behavioral (agitation) function. Results: In linear mixed models, physical activity depressive symptoms improved more with PAL. Conclusion: Evidence supports that the PAL program helps preserve/enhance function of AL residents with CI. Additional study is required to evaluate the duration and predictors of effectiveness of the PAL intervention.